2014
DOI: 10.1080/07908318.2014.912658
|View full text |Cite
|
Sign up to set email alerts
|

‘Glued to the family’: the role of familism in heritage language development strategies

Abstract: This article, part of a larger ethnographic study, examines how a family's affective ties to the country of origin and to relatives still residing there supported their Spanish language development and maintenance efforts in Vancouver, Canada. Drawing on data from participant observation and interviews, the article analyses the parents' diverse heritage language development (HLD) strategies and ideologies and the children's affective connections to family members in Perú. The analysis draws attention to the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…Parents should also be aware of the influence of communicative style on language outcomes. For example, evidence indicates that the promotion of relational warmth and autonomy during parental interactions promotes language learning and might promote more positive relationships (Guardado & Becker, 2014). This study indicates the potential necessity of communicatively respecting and recognizing ethnic diversity between family individuals while also establishing strategies to maintain a sense of family membership within individual relationships and roles.…”
Section: Resultsmentioning
confidence: 99%
“…Parents should also be aware of the influence of communicative style on language outcomes. For example, evidence indicates that the promotion of relational warmth and autonomy during parental interactions promotes language learning and might promote more positive relationships (Guardado & Becker, 2014). This study indicates the potential necessity of communicatively respecting and recognizing ethnic diversity between family individuals while also establishing strategies to maintain a sense of family membership within individual relationships and roles.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies suggest that the maintenance of heritage language is more the concern of parents than of the young people (Clyne, 2005;Guardado & Becker, 2014;Ghuman, 2001). In this study, parents have made a significant effort to maintain Bahasa Indonesia by speaking the language with their children, inside and outside of home.…”
Section: Possible Challenges In the Use Of Bahasa Indonesiamentioning
confidence: 95%
“…Parents are the first agents that introduce children to their heritage culture. Studies have shown that families provide an important context for heritage language maintenance (Phinney, 1990;Guardado & Becker, 2014) including among African and Asian families in Australia (Lee, 2002;Tam & Lee, 2010;Ndhlovu, 2010;Mu, 2014). Ethnic identity socialization practices by families include speaking the ethnic language and participating in cultural and religious festivals (Moua & Lamborn, 2010).…”
Section: Family As Agency Of Ethnic and Religious Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has noted that parents' choice of language and implementation of literacy practices with children can contribute significantly to the maintenance of these languages (e.g. Garcia, 2003;Guardado & Becker, 2014;Kosonen, 2008). To understand parents' family language policy decisions, it has become important for researchers to appreciate the ideological beliefs, attitudes and efforts of the parents with regard to these decisions (e.g.…”
Section: Introductionmentioning
confidence: 99%